Feasibility of diffusion kurtosis imaging in evaluating cervical spinal cord injury in multiple sclerosis - Bian, BingYang; Zhou, BoXu; Shao, ZhiQing; Zhu, XiaoNa; Jie, YiGe; Li, Dan (Medicine (Baltimore), 2023)
This research aimed to assess gray matter (GM), white matter (WM), lesions of multiple sclerosis (MS) and the therapeutic effect using diffusion kurtosis imaging (DKI). From January 2018 to October 2019, 78 subjects (48 of MS and 30 of health) perform routine MR scan and DKI of cervical spinal cord. The MS patients were divided into 2 groups according to the presence or absence of T2 hyperintensity. DKI-metrics were measured in the lesions, normal-appearing GM and WM. Significant differences were detected in DKI metrics between MS and healthy (P < .05) and between patients with cervical spinal cord T2-hyperintense and without T2-hyperintense (P < .001). Compared to healthy, GM-mean kurtosis (MK), GM-radial kurtosis, and WM-fractional anisotropy, WM-axial diffusion were statistically reduced in patients without T2-hyperintense (P < .05). Significant differences were observed in DKI metrics between patients with T2-hyperintense after therapy (P < .05), as well as GM-MK and WM-fractional anisotropy, WM-axial diffusion in patients without T2-hyperintense (P < .05); Expanded Disability Status Scale was correlated with MK values, as well as Expanded Disability Status Scale scores and MK values after therapy. Our results indicate that DKI-metrics can detect and quantitatively evaluate the changes in cervical spinal cord micropathological structure.